CEO's political connections, institutions and audit opinions. Issue 3 (7th August 2017) - Hu, Fang; Stewart, Jenny; Tan, Weiqiang
Abstract : Purpose: The purpose of this paper is to investigate whether audit opinions of listed firms in China vary systematically with the political connections of the firm's chief executive officer (CEO). Prior literature only shows the importance of political influence to auditor choice and audit quality. Design/methodology/approach: A politically connected firm is defined as a firm in which the CEO has a political background. The authors use a "difference-in-difference" model to control for self-selection problems. Findings: The authors find that the likelihood of receiving a favourable opinion in the subsequent period is positively associated with a CEO's political connections. This positive association is stronger with CEOs connected to local government within the same region. The authors further find that the CEO's political connections have more influence on favourable audit opinions in non-state-owned enterprises (non-SOEs) in a less developed and lower investor protection region. The influence is also less significant in the regions where there are more non-state-owned or foreign banks and where there are greater penalties for political corruption and relationship-based contracting. Originality/value: The study complements and extends the existing literature on the role of political connections in the economy by providing evidence on the effect of a CEO's political connections on audit opinions. The authors extend the research on auditing in emerging markets by explicitly accounting for unique institutional and market factors in China. They explore audit quality by observing how audit opinions are directly shaped by political and institutional factors.